OMT121 : Document processing I / Faculty of Business Management - UiTM, Faculty of Business Management (Universiti Teknologi MARA (UiTM), 2018)
This course is designed to train students to use the current word processing software to enable students to become familiar with the computer keyboard, basic components of the micro-computer and relevant peripheral equipment. Upon achieving basic word processing skills, students will be able to type English passages accurately by using correct keyboarding at a minimum speed of 30 word per minute (wpm) and produce the following documents: business letters, reports, memorandums and tables. This course will emphasize accurate document processing and proofreading skills as well as acquiring good work habits.